PENGARUH KOMUNIKASI DAN MOTIVASI TERHADAP KINERJA BISNIS PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. CABANG ISKANDAR MUDA MEDAN - Triana Dewi Pakpahan Anna Pakpahan; Lucy Anna Lucy Anna (Universitas Sumatera Utara, 2013)
ABSTRACT INFLUENCE OF COMMUNICATION AND MOTIVATION ON BUSINESS PERFORMANCE IN PT BANK RAKYAT INDONESIA (Persero) Tbk. Branch of MEDAN ISKANDAR MUDA The purpose of this survey is to know the influence to analyze of communication and motivation on business performance in PT Bank Rakyat Indonesia (Persero) Tbk. Branch of Medan Iskandar Muda. This research is a causal type, Data used in this research is the primary data and secondary data. Data analysis methods used is descriptive quantitative by using multiple linear regression. The population in this study were a total 50 respondents for study the sample, with saturation sampling technique. The study showed that the variable communication in a positive and not significant influence but to a variable motivation in a positive effect and significant to employee performance in PT Bank Rakyat Indonesia (Persero) Tbk. Branch of Medan Iskandar Muda. KeywordsCommunication, Motivation, Business Performance